METODE TARGHIB DAN TARHIB DALAM MEMBENTUK AKHLAK SISWA SEKOLAH DASAR - Jabar Idharudin, Abdul; Samsuddin, Samsuddin; M. Yusup, Aditya; Nur Shamsul, Mariyanto (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
A series of social deviance incidents among students has caused widespread concern, highlighting the importance of researching the implementation of effective educational methods to shape the character of elementary school students. Early habituation to noble character is essential to nurture a generation with bright futures. This study employs a qualitative method, gathering data through observation, interviews, and documentation, and analyzing it through descriptive interpretative techniques. The research focuses on SDIT Al-Hidayah Bogor. The findings reveal that the implementation of the Targhib and Tarhib methods in shaping students' character is carried out systematically through the use of effective strategies integrated into a conducive school system and environment. Consequently, the learning process and school programs synergize to foster students' character development in the school, family, and community settings